2019
DOI: 10.3390/cells8050495
|View full text |Cite
|
Sign up to set email alerts
|

NDRG2 Sensitizes Myeloid Leukemia to Arsenic Trioxide via GSK3β–NDRG2–PP2A Complex Formation

Abstract: N-Myc downstream-regulated gene 2 (NDRG2) was characterized as a tumor suppressor, inducing anti-metastatic and anti-proliferative effects in several tumor cells. However, NDRG2 functions on anticancer drug sensitivity, and its molecular mechanisms are yet to be fully investigated. In this study, we investigated the mechanism of NDRG2-induced sensitization to As2O3 in the U937 cell line, which is one of the most frequently used cells in the field of resistance to As2O3. NDRG2-overexpressing U937 cells (U937-ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[14] found that the expression of p-GSK-3β in the arsenic intervention group was higher than the control group (P<0.05), which induced MCL cells apoptosis (Jeko-1, Granta-519). For wild-type myelogenous leukemia cells (U937-∆C NDRG2) [15], there were no significant difference in GSK-3β and Mcl-1 protein expression between the As2O3 group and the control group (P>0.05). Nowadays, the regulation of arsenic on GSK-3β is still unclear, and the systematic reviews of the relationship between arsenic and GSK-3β have not been reported.…”
Section: Introductionmentioning
confidence: 88%
“…[14] found that the expression of p-GSK-3β in the arsenic intervention group was higher than the control group (P<0.05), which induced MCL cells apoptosis (Jeko-1, Granta-519). For wild-type myelogenous leukemia cells (U937-∆C NDRG2) [15], there were no significant difference in GSK-3β and Mcl-1 protein expression between the As2O3 group and the control group (P>0.05). Nowadays, the regulation of arsenic on GSK-3β is still unclear, and the systematic reviews of the relationship between arsenic and GSK-3β have not been reported.…”
Section: Introductionmentioning
confidence: 88%
“…NDRG2 also enhanced the sensitivity of an ovarian cancer cell line, SKOV-3, to pazopanib by activating the SK1/JNK1 signaling pathway [68]. NDRG2 enhanced the sensitivity to cisplatin and As 2 O 3 in a p53 loss-of-function mutant myeloma cell line, U937 [69,70]. The degradation of Mcl-1 and the increase in Bak was mediated by JNK activation [71] and an increase in phospho-eIF2α, respectively, in NDRG2-overexpressed U937 cells after cisplatin treatment [69].…”
Section: Sensitivity To Anticancer Drugs and Ndrg2mentioning
confidence: 99%
“…NDRG2 overexpression induced Mcl-1 degradation and apoptosis through GSK3β activation. NDRG2 mediated the interaction between GSK3β and protein phosphatase 2A (PP2A), inducing the dephosphorylation of GSK3β at S9 by PP2A [70]. The interaction between NDRG2 and PP2A also activated PTEN, inhibiting AKT activation associated with cell survival and tumorigenesis [15,77].…”
Section: Sensitivity To Anticancer Drugs and Ndrg2mentioning
confidence: 99%
“…Evidence suggests that GSK3α/β plays a central role in a variety of different signaling pathways that are relevant to macrophage function including polarization [ 41 , 42 , 43 , 44 ], inflammatory response [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], unfolded protein response [ 28 , 40 , 41 , 42 , 43 ], glucose [ 58 , 59 , 60 , 61 ] and lipid [ 28 , 62 ] metabolism, viability [ 17 , 28 , 63 , 64 , 65 ], migration [ 66 , 67 , 68 ], and proliferation [ 69 , 70 , 71 , 72 ] ( Figure 3 ). Here, we summarize the current literature on the role of GSK3α/β in regulating specific macrophage functions.…”
Section: Glycogen Synthase Kinasementioning
confidence: 99%
“…Activated GSK3α/β phosphorylates myeloid cell leukemia (Mcl)-1, resulting in Mcl-1 degradation followed by apoptosis [ 63 ]. In U937 cells (an acute myeloid leukemia cell line), a complex of N-Myc downstream-regulated gene 2 (NDRG2), GSK3α/β, and PP2A is formed upon treatment with the anti-cancer drug As2O3 [ 64 ]. This leads to GSK3α/β activation through dephosphorylation at Ser9 by PP2A, followed by Mcl-1 degradation and apoptosis [ 65 ].…”
Section: Gsk3α/β—regulation Of Macrophage Functionmentioning
confidence: 99%